PSYCHOANALYTICALLY INFORMED PLAY THERAPY fantasy -exposure life-narrative therapy. - Steadman, Jason L. ([S.l.] : ROUTLEDGE, 2024)
Psychoanalytically Informed Play Therapy: Fantasy-Exposure Life-Narrative Therapy is a structured manual for the execution of FELT, an integrative play therapy that marries the analytic, relational, and psychodynamic aspects of traditional Play Therapy with the scientific rigor and replicability standards of clinical empiricism. Jason Steadman's FELT model creates a structured, empirically derived means of monitoring children's play using psychoanalytic methods. Steadman's method proposes the usage of story stems to structure play to address critical needs in children's psychological development. In FELT, Steadman teaches readers how to identify problematic play themes and how to respond therapeutically to drive play and general child development toward healthy directions. Steadman uses anxiety as the primary example of psychological distress for FELT, but also shows how the method can be applied to many other pathologies, such as depression and trauma. Steadman explains 11 core FELT themes, which are then further condensed to three major clinical targets identified in the play of clinically anxious children. Each of these is described in detail in the book and therapists are shown not only how to reliably identify themes, but how to focus their interventions to move children toward major play-based targets. Integrating psychoanalytic theory with an emphasis on Object Relations, Steadman's FELT program highlights the importance of the self in healthy child development and how play-based psychotherapy can be used to help children build stronger, healthier selves that can face a wide variety of psychological issues across their lifespan. Including comprehensive theoretical underpinnings and thorough clinical examples of FELT at work, this volume will allow therapists, clinicians, and mental health workers to understand childhood play in an empirically based manner and show them how to integrate the key tenets of FELT into their own work to better aid children experiencing anxiety and other mental health concerns.
Keywords: Play therapy; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Psychotherapy / Child & Adolescent